2016
DOI: 10.1016/j.mod.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The importance of basonuclin 2 in adult mice and its relation to basonuclin 1

Abstract: BNC2 is an extremely conserved zinc finger protein with important functions in the development of craniofacial bones and male germ cells. Because disruption of the Bnc2 gene in mice causes neonatal lethality, the function of the protein in adult animals has not been studied. Until now BNC2 was considered to have a wider tissue distribution than its paralog, BNC1, but the precise cell types expressing Bnc2 are largely unknown. We identify here the cell types containing BNC2 in the mouse and we show the unexpect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…In addition, a zincfinger-containing protein, Basonuclin 2 (Bnc2) was also among the most highly enriched genes overall. While not a classical transcription factor, by virtue of its zinc finger domain and nuclear localization signal, Bnc2 regulates transcriptional events (Vanhoutteghem et al, 2016). A recent report that used a LacZ reporter mouse demonstrated that in the central nervous system, Bnc2 is only expressed in a small subset of dorsal horn cells (Vanhoutteghem et al, 2016), which is consistent with our transcriptomic results.…”
Section: Transcription Factorssupporting
confidence: 91%
“…In addition, a zincfinger-containing protein, Basonuclin 2 (Bnc2) was also among the most highly enriched genes overall. While not a classical transcription factor, by virtue of its zinc finger domain and nuclear localization signal, Bnc2 regulates transcriptional events (Vanhoutteghem et al, 2016). A recent report that used a LacZ reporter mouse demonstrated that in the central nervous system, Bnc2 is only expressed in a small subset of dorsal horn cells (Vanhoutteghem et al, 2016), which is consistent with our transcriptomic results.…”
Section: Transcription Factorssupporting
confidence: 91%
“…In addition, a zinc-finger-containing protein, Basonuclin 2 ( Bnc2 ) was among the most highly enriched genes overall. While not a classical transcription factor, by virtue of its zinc finger domain and nuclear localization signal, Bnc2 regulates transcriptional events 49 . A recent report that used a LacZ reporter mouse demonstrated that in the central nervous system, Bnc2 is only expressed in a small subset of dorsal horn cells 49 , which is consistent with our transcriptomic results.…”
Section: Resultsmentioning
confidence: 99%
“…BNC2 is a zinc-finger transcription factor that appears to be necessary for development of craniofacial and long bones as well as ectodermal appendages (hair follicles, salivary glands, palatal rugae) 47 , 48 , and it has previously been associated with skin pigmentation and pigmented spots 11 , 12 , 49 . Epigenetic and eQTL data indicate the most likely function for the signal’s variants are as an enhancer for an alternative promoter near BNC2 exon 3 10 .…”
Section: Discussionmentioning
confidence: 99%